Economics - Burneo Farfan, Kurt (2015)
Microeconomic issues. Economics fundamentals. Concepts and principles. Demand and supply. Elasticity, efficiency and equity in a competitive market. Consumer theory. Consumption optimization. Theory of the firm. Production organization. Production, costs and firm decisions. Perfect and imperfect competition markets. International Trade. Macroeconomic issues. Main macroeconomic aggregates. The full-employment economy, labour market and potential GDP. Money, inflation and the price level. Aggregate supply and demand and the multiplier. Fiscal and monetary policy. Macroeconomics of open economies. New concepts about the economy - The economy in the digital age. The economics of information and communications; and the Global economy. Biodiversity and Economics. Growth and development: Convergent concepts?. New technological development and challenges for the Economy. APPENDIX 1: Special topics on Peru. APPENDIX 2: Elementary mathematics for understanding economics. Bibliography.